Innovation to Prevent Premature Aging by Utilizing Coffee Grounds Waste in Makassar - Islamiah, Farida; Darmawan, Dedy (STIE Amkop Makassar, Indonesia, 2024)
Premature aging is a growing concern in modern society, and innovative solutions are increasingly being sought to address this issue. One such innovation is the use of coffee grounds waste, a byproduct often discarded after brewing. This study explores the potential of utilizing coffee grounds waste as an ingredient in anti-aging products, particularly in the context of Makassar, a region with a rich coffee culture. Coffee grounds are rich in antioxidants, caffeine, and bioactive compounds that can provide protective benefits to the skin, improving elasticity and reducing the appearance of fine lines. The research examines the properties of coffee grounds, their application in skincare, and the potential for sustainable practices in utilizing waste material to create natural, eco-friendly anti-aging products. By focusing on local resources, this innovation presents a promising solution to not only mitigate premature aging but also contribute to waste reduction and environmental sustainability in Makassar